Pierre Monnet, Karel IV. Evropský císař, Praha 2023 - Jan Boukal (Acta Universitatis Carolinae: Historia Universitatis Carolinae Pragensis)
Book review on Pierre Monnet, Karel IV. Evropský císař, Karolinum, Praha 2023, 301 stran, ISBN: 978-80-246-5709-7